Faktor Fleksibilitas, Panjang Tungkai, dan Kekuatan: Bagaimana Korelasinya dengan Performa Gyaku Tsuki? - Widhiantoro, Ridho Bayu; Febriani, Ayu Rizky; Listiandi, Arfin Deri; Ngadiman, Ngadiman; Wahono, Bayu Suko; Khurrohman, Moch Fath (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2024)
This study aimed to investigate the relationship between leg length, waist flexibility, and arm muscle strength and Gyaku Tsuki's punch speed in karate martial arts. A total of 30 karateka (age = 16.4 ± SD = 0.626) participated in the study. Leg length was measured using anthropometric methods, waist flexibility was measured by sit and reach tests, arm muscle strength was measured by push-up tests, and Gyaku Tsuki's punch speed was measured using Kinovea software. The results showed that leg length, waist flexibility, and arm muscle strength had a significant positive relationship with Gyaku Tsuki's punch speed (p = 0.000 0.005). This research can be the basis for further research in the field of kinematics and movement kinetics in the context of martial arts.